Ibn Khaldun's Thoughts on Islamic Education (Instrumental Pragmatist) and Their Relevance to Contemporary Islamic Education - Ikhsan Kamil; Khoirul Amin (UMSU, 2023)
The 21st century demands a quick and appropriate response from the Islamic education system as a whole, so that Islamic education in the future will need to continue to improve, both in terms of curriculum and Islamic educational institutions. The urgency and purpose of this study is to describe Ibn Khaldun's view of Islamic education and its relevance to contemporary Islamic education. This research used library research with primary sources in the form of Ibn Khaldun's book al-muqaddimah and secondary sources in the form of books and journals relevant to this research whose data were analysed through content analysis. The results of this study indicate that Ibn Khaldun's idea of Islamic education consists of educators and students, curriculum, materials and learning methods. And also Ibn Khaldun belongs to the pragmatic-instrumental stream of education in which this school has the first criterion, the teachings and values contained in the Al-Qur'an and Sunnah are still understood by not letting go and still taking into account the concrete situation of the dynamics of the association, the classical and contemporary eras that surround it. Secondly, Islamic education is always based on concepts that pay attention to practical benefits. Thirdly, philosophical thinking that is always general/universal in nature so that it can be applied in all places, circumstances and changing times. The relevance of Ibn Khaldun's thought to contemporary Islamic education is that Islamic education can adapt to the times and have practical value.